Economic generation schedule on thermal power system considering emission using grey wolves optimization. (June 2017) - Kadali, Kalyan Sagar; Rajaji, L.; Moorthy, V.; Viswanatharao, J.
Abstract: This paper delineates a computational framework to ascertain optimum thermal generation schedule using newfangled grey wolves optimization (GWO) technique corresponding to economic, emission, and combined economic emission operation. This scheduling problem is devised as a bi-objective optimization and linear interpolated price penalty model is developed based on simple analytical geometry equations which blends two conflict objectives perfectly. In order to obtain high-quality solutions within lesser executing time, the algorithm parameters are nicely replaced with system parameters that carry out global and local search process in the feasible region collaboratively. Further, an appropriate constraint handling mechanism is suitably incorporated in the algorithm that intern produces a stable convergence characteristic. The effectiveness of the proposed approach is illustrated on six unit thermal systems with due consideration of transmission line loss. The desired GWO technique reports a new feasible solution for quadratic cost model which is compared with the solution that has evolved earlier and the comparison shows that the GWO technique has outstripped other algorithms effectively.